ANALISIS STRES KERJA PADA PELAKU USAHA KECIL DAN MENENGAH TERHADAP KINERJA USAHA: (Studi Kasus Usaha Rumah Makan Mbah Suro Kec. Temon) - Triana Rahayu; Alkadri Kusalendra Siharis (Transpublika Publisher, 2022)
This study aims to (1) analyze factors that cause stress in the workplace (stressor) that occured in Mbah Suro's restaurant, (2) analyze the impact of work stress towards business performance at Mbah Suro's restaurant. This study used qualitative descriptive research method with case studies. Data were collected through interview and observation. In this study, data testing was carried out using triagulation. Stress in the workplace which occurred at Mbah Suro's restaurant business emerged from internal and external environmental factors. The internal factor of work stress experienced by business owners derived from the employees. While, the external factors of work stress acquired from consumers, competitors, local governments, and natural disasters such as pandemics, as well as role conflicts. It is expected that this study results could contribute to restaurant business owners to manage work stress management professionally, which will impact on the business performance. Further studies need to be carried out by using different methodologies in measuring and analyzing stress in the workplace.